Genotyping, local prevalence and international dissemination of β‐lactamase‐producing Kingella kingae strains. (14th June 2014) - Basmaci, R.; Bonacorsi, S.; Bidet, P.; Balashova, N. V.; Lau, J.; Muñoz‐Almagro, C.; Gene, A.; Yagupsky, P.; Tassios, P.
Abstract β‐lactamase production has been sporadically reported in the emerging Kingella kingae pathogen but the phenomenon has not been studied in‐depth. We investigated the prevalence of β‐lactamase production among K. kingae isolates from different geographical origins and genetically characterized β‐lactamase‐producing strains. Seven hundred and seventy‐eight isolates from Iceland, the USA, France, Israel, Spain and Canada were screened for β‐lactamase production and, if positive, were characterized by PFGE and MLST genotyping, as well as rtxA, por, blaTEM and 16S rRNA sequencing. β‐lactamase was identified in invasive strains from Iceland (n = 4/14, 28.6%), the USA (n = 3/15, 20.0%) and Israel (n = 2/190, 1.1%) and in carriage strains in the USA (n = 5/17, 29.4%) and Israel (n = 66/429, 15.4%). No French, Spanish or Canadian isolates were β‐lactamase producers. Among β‐lactamase producers, a perfect congruency between the different typing methods was observed. Surprisingly, all US and Icelandic β‐lactamase‐producing isolates were almost indistinguishable, belonged to the major international invasive PFGE clone K/MLST ST‐6, but differed from the four genetically unrelated Israeli β‐lactamase‐producing clones. Representative strains of different genotypes produced the TEM‐1 enzyme. K. kingae β‐lactamase producers exhibit a clear clonal distribution and have dissimilar invasive potential. The presence of the enzyme in isolates belonging to the major worldwide invasive clone K/ST‐6 highlights the possible spread of β‐lactam resistance, and emphasizes the importance of routine testing of all K. kingae clinical isolates for β‐lactamase production.